Synergistic effect of Ru-N₄ sites and Cu-N₃ sites in carbon nitride for highly selective photocatalytic reduction of CO₂ to methane - Zeng, Lei (2022)
Developing single-atom photocatalysts for selective conversion of CO2 to valuable fuel is of great attraction but remains challenging. In this work, ruthenium and copper single atoms are for the first time simultaneously incorporated into polymeric carbon nitride (PCN) through a simple preassembly-coprecipitation-pyrolysis process. The obtained PCN-RuCu sample exhibited much higher selectivity (95%) for CH4 production than the individual Ru or Cu decorated PCN during photocatalytic CO2 reduction under visible-light irradiation. The atomically dispersed Ru-N4 and Cu-N3 moieties were confirmed by spherical aberration-corrected electron microscopy and extended X-ray absorption fine structure spectroscopy. Density function theory (DFT) calculations revealed that the co-existence of Ru-N4 sites and Cu-N3 sites can effectively tune the electronic structure of PCN, making the Ru sites account for photogenerated electron-hole pairs and the Cu sites for CO2 hydrogenation. Moreover, the synergetic effect between Ru and Cu single atoms significantly promotes the consecutive hydrogenation processes of *CO species towards CH4 production. Our studies provide a new understanding of the mechanism for photocatalytic reduction of CO2 to CH4, and pave a new way to design photocatalysts for the selective production of solar fuels.